1965
DOI: 10.1139/v65-251
|View full text |Cite
|
Sign up to set email alerts
|

Fully Fluorinated Alkoxides: Part I. Trifluoromethoxides of Alkali Metals

Abstract: The preparation is described of the trifluoromethoxides of the heavier alkali metals, i.e. MOCF, where M = K, Rb, or Cs. These are stable, crystalline, ionic solids made by the reversible reaction of carbonyl fluoride with the appropriate metal fluoride. No trifluoromethoxides could be prepared from lithium, sodium, barium, or thallium(1) fluorides. Factors affecting the relative stability of such compounds are discussed.Trifluoromethanol, CFBOH, is not known, and is generally assumed to be incapable of existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(44 citation statements)
references
References 4 publications
(1 reference statement)
4
36
0
1
Order By: Relevance
“…The yields of perfluorinated methyl vinyl ether and tetrafluoroethylene were 30 and 60 mol %, respectively. With Na + replaced by K + , the yield of tetrafluoroethylene increases from 60 to 95 mol %, suggesting stabilization of the trifluoromethoxide anion with the potassium ion, in agreement with the data of [5,6]. …”
supporting
confidence: 91%
See 1 more Smart Citation
“…The yields of perfluorinated methyl vinyl ether and tetrafluoroethylene were 30 and 60 mol %, respectively. With Na + replaced by K + , the yield of tetrafluoroethylene increases from 60 to 95 mol %, suggesting stabilization of the trifluoromethoxide anion with the potassium ion, in agreement with the data of [5,6]. …”
supporting
confidence: 91%
“…Low-boiling gases were passed through a trap with liquid bromine and then through an alkaline absorber. From the trap, we isolated 4 g (yield~15%) of a product identified as perfluoro-2-methyloxolan-3-one VIII by comparison of the 19 F NMR and mass spectra with those reported in [6]; bp~15oC. In the trap with bromine, 1,2-dibromotetrafluoroethane was obtained as a separate phase.…”
Section: Pyrolysis Of Perfluoro-2-bromopropionyl Fluoride VImentioning
confidence: 99%
“…An important observation made early on was that the kinetic performance of Cs 18 F in the [ 18 F] exchange reactions could be improved significantly if the compound had been activated by prior formation and subsequent thermal decomposition of the alkoxides, Cs + [OC 18 F(CF 3 ) 2 ] À or Cs + [OCF 2 18 F] À1 [14]. These are available readily by reaction between CsF and (CF 3 ) 2 CO or F 2 CO [17]. The treatment introduces an extra stage into the labelling process but is justified by the increased level of [ 18 F] incorporation achievable.…”
Section: Synthesis Of Some Radio Labelled Probe Compoundsmentioning
confidence: 99%
“…Several teams tried to draw this equilibrium towards CF 3 O À and demonstrated that if fluorides are associated with rather bulky cations [CsF, [23,24] (Me 2 N) 3 S + Me 3 SiF 2 À [25] ], the resulting trifluoromethoxide could be stable enough, in solution, to react with reactive electrophiles such as benzyl bromide [24] or primary triflates and bromides. [26] Nevertheless, the development of this reaction was limited by the high toxicity of gaseous fluorophosgene.…”
Section: Introductionmentioning
confidence: 99%